The Improvement of Mathematical Problem Solving Ability and Self-Efficacy Students through Problem-Based Learning Model (International Journal of Scientific Research and Management (IJSRM), 2020)
This study aims to determine the improvement of problem solving ability of mathematics and self-efficacy of students through problem-based learning model. This research method used pre-test post-test control group design. The population in this study is all of Year 7 students of SMP Negeri 10 Banda Aceh. Two classes of samples were randomly selected, the experimental and the control classesThe research instrument consisted of a mathematical problem solving test and self-efficacy questionnaire. Data analysis was using t-test statistic. The result of the research showed 1) mathematical problem solving ability of students through problem-based learning model better than students who received conventional learning, 2) Self-efficacy of students who through problem-based learning model better than students who learn conventionally.